LC-MS ANALYSIS AND PHARMACOLOGICAL POTENTIAL OF HYPERFORIN AND HYPERICIN FROM HYPERICUM HOOKERIANUM WIGHT AND ARN. - NARAYANAN RAVISANKAR,; CHANDRASEKARAN SIVARAJ,; SOORIAMUTHU SEENI,; JERRINE JOSEPH,; NANJIAN RAAMAN, (International Journal of Pharma and Bio Sciences, 2014)
The work was aimed to develop a method for extraction and identification of the marker compounds of Hypericum species, hyperforin and hypericin present in the buds and leaf extracts of Hypericum hookerianum, a lesser known species of Asia. LC-MS hyphenated techniques were used and the data indicated the presence of both these active compounds in the methanol extract of both buds and leaves. ABTS·+ (2, 2´-azinobis [3-ethylbenzthiazoline]-6-sulfonic acid) radical cation scavenging assay using the extract showed concentration dependent increase in inhibition indicating free radical scavenging and antioxidant properties. Further, the extract (500µg) showed a broad spectrum antibacterial activity especially against the drug resistant Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumonia and Salmonella typhimurum which is characteristic of hyperforin. Hyperforin and hypericin when docked with the protein tyrosine kinase C using bioinformatics tools predicted anticancer potential of the extract to be validated by wetlab experiments. The results suggest methanolic extract of Hypericum hookerianum is a valuable commodity with potent antibacterial and anticancer activities. Though the shoot extracts of Hookerianum are reported to be antiHSV-1, the extracts subjected to P-24 antigen assay for HIV screening in the present investigation did not yield positive results upto 300 µg.